2007
DOI: 10.1007/s00256-007-0368-5
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional spin-lock magnetic resonance imaging of the shoulder joint at 3 T: initial experience

Abstract: We demonstrated that 3D-T(1rho) MRI of the shoulder can be performed on a 3 T clinical scanner within specific absorption rate (SAR) limits, and we present baseline values for healthy patients which may be useful for quantitative comparison with diseased shoulders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…A composite spin‐lock pulse showing the tolerance to shimming and RF errors was designed to allow spin locking with relatively weak RF (low spin‐lock frequency) and therefore low specific energy absorption rate (SAR) . A “self‐compensated” spin‐locking pulse with the phase of the second half of the spin‐lock pulse being shifted 180° from the first half was proposed to reduce the artifacts due to the B 1 inhomogeneity. Application of spin‐locking pulses in a system with species at a range of chemical shifts or in a system with significant B 0 inhomogeneity can result in more complex rotations arising from off‐resonance spin‐locking.…”
Section: History Of T1ρ Pulse Sequence Developmentmentioning
confidence: 99%
“…A composite spin‐lock pulse showing the tolerance to shimming and RF errors was designed to allow spin locking with relatively weak RF (low spin‐lock frequency) and therefore low specific energy absorption rate (SAR) . A “self‐compensated” spin‐locking pulse with the phase of the second half of the spin‐lock pulse being shifted 180° from the first half was proposed to reduce the artifacts due to the B 1 inhomogeneity. Application of spin‐locking pulses in a system with species at a range of chemical shifts or in a system with significant B 0 inhomogeneity can result in more complex rotations arising from off‐resonance spin‐locking.…”
Section: History Of T1ρ Pulse Sequence Developmentmentioning
confidence: 99%
“…T1rho (or T1ρ- T1 relaxation time in the rotating frame)-weighted MR imaging has recently been proposed as a promising alternative biomarker to existing conventional morphological MRI methods (1416). Related techniques have been used to investigate the slow motion interactions between macromolecular protons and bulk water.…”
Section: Introductionmentioning
confidence: 99%
“…Related techniques have been used to investigate the slow motion interactions between macromolecular protons and bulk water. Previous studies have shown that T1rho mapping is sensitive to biochemical changes in proteoglycan (PG) loss in hyaline cartilage (14, 15, 17, 18) and menisci (19, 20) with early OA. T1rho mapping technique may be a pre-structural indicator of OA (16, 19, 20).…”
Section: Introductionmentioning
confidence: 99%
“…Although others have imaged glenohumeral cartilage using T2 mapping 9 , our study, along with that of La Rocca Vieira et al 7 , is among the first to image glenohumeral cartilage with T1ρ MRI. Furthermore, to our knowledge, our study is the first to use biochemical MRI sequences to evaluate glenohumeral cartilage damage after anterior shoulder dislocation.…”
Section: Discussionmentioning
confidence: 73%
“…While there was little difference in T1ρ values across zones in glenoid cartilage, inferior humeral head cartilage tended to have higher T1ρ values than superior zones in healthy controls. Previously, La Rocca Vieira et al performed T1ρ MRI mapping in four healthy controls to determine baseline T1ρ values for glenoid and humeral head cartilage 7 . They found baseline T1ρ values of 32.4 – 36.9ms for glenoid cartilage and 37.9 – 48.5ms in humeral head cartilage.…”
Section: Discussionmentioning
confidence: 99%